HUBUNGAN PENERIMAAN DIRI DENGAN KUALITAS HIDUP PASIEN HIV/AIDS DI POLI VCT RSUP DR. M. DJAMIL TAHUN 2023 - Bantar, Kevin; Liza, Rini Gusya; Burhan, Ida Rahmah; Yanis, Amel; Firdawati, Firdawati; Fadrian, Fadrian (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
HIV/AIDS has been a global health issue for many years. This chronic condition affects multiple aspects of life and acts as a significant stressor that reduces patients’ quality of life. People living with HIV/AIDS (PLWHA) often face limitations in daily activities, making it difficult to accept their identity and life circumstances. This study aimed to analyze the relationship between self-acceptance and quality of life among HIV/AIDS patients at the VCT Clinic of Dr. M. Djamil General Hospital in 2023. An analytical cross-sectional design was used with purposive sampling, involving 84 participants. Data collection took place from November 2022 to November 2023 using the USAQ and WHOQOL HIV-BREF questionnaires. Data were analyzed using Pearson correlation tests. Results showed a positive and significant correlation between self-acceptance and quality of life (p = 0.034; r = 0.231). Significant relationships were also found with the physical (p = 0.012; r = 0.272) and psychological (p = 0.014; r = 0.269) domains. In conclusion, self-acceptance is positively associated with overall quality of life, particularly in physical and psychological aspects, among HIV/AIDS patients.